The Role of Extrabudgetary Funds in the Management of Budgetary Organizations (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article examines the role and significance of extra-budgetary funds in the management of budgetary organizations. Extra-budgetary funds provide additional financial resources to implement strategic projects and improve the quality of services, which is especially important in conditions of limited government budgets. The sources of the formation of extra-budgetary funds, such as commercial activities, donations and investments, as well as the directions of their use, including infrastructure development, scientific research and social programs, are considered.